Influência do espaçamento e densidade de hastes em café conilon conduzido com a poda programada de ciclo - Verdin Filho, Abraão Carlos (2011)
Proper management through the use of new techniques has been paramount to the success of good productivity in the coffee culture conilon. Aiming to improve the information management now in place for the culture, related to the spacing of plants in the ar